(untitled) (De Legibus - Law Journal, 2024)
In this text we intend to contribute to the interpretation of the concepts of place of work, working time and nexus of causality as elements of the concept of work accident provided in the Work Accidents and Occupational Diseases Compensation Scheme, with the aim of clarifying these concepts in light of telework performed at the worker’s home, in offline and one way line telework modalities. And also propose some solutions to the issues that we consider to be open, despite the legislative changes introduced by Law no. 83/2021, of 6th December.